Feasibility and cross-cultural validation of an adapted social skills group training programme (KONTAKTTM CHILD) for Chinese autistic children: a waitlist RCT protocol - Sven Bölte; Peipei Yin; Uchong Lao; Huilin Zhu; Fengjing Liang; Wuxia Bai; Xiaoqian Huang; Sonya Girdler; Xiaobing Zou (BMJ Open)
Introduction School-age autistic children commonly experience social communication and interaction challenges in their everyday lives. While international evidence suggests that social skills group training (SSGT) programmes can support autistic children, improving their psychosocial functioning, to date there is no standardised evidence-based SSGT tailored towards the needs of autistic children aged 8–12 years living in the Chinese Mainland. Therefore, the primary objective of this study will be to evaluate the feasibility and acceptability of a culturally adapted 16-session version of the social skills programme KONTAKT in Chinese autistic children. Additionally, preliminary efficacy and cost-effectiveness will be assessed to inform a future definitive trial.Methods and analysis This study will employ a randomised, single-blinded, waitlist-controlled feasibility design with 36 Chinese autistic children aged 8–12 years with IQ over 70 referred to the Child Development and Behavior Center in Guangzhou, China. Participants will be randomly assigned to either the immediate training group or the delayed training group stratified by sex. Feasibility will be assessed using quantitative and qualitative data obtained from the KONTAKT CHILD participants, their parents and facilitators of the programme. Preliminary efficacy and cost-effectiveness are assessed via quantitative data obtained at five time points. The primary efficacy outcome is participants’ improvement in social skills as measured by the Contextual Assessment of Social Skills. Other outcomes include parents and teachers’ reports of participants’ autistic traits and adaptive functioning, participants’ self-report and projective tests for self-assertiveness and psychosocial functioning, and parent reports on parental reflective functioning and perceived school support. Common process factors and their effects on outcomes will also be explored. Cost-effectiveness will consider from both societal and healthcare perspectives.Ethics and dissemination The current study protocol has been reviewed and ethics approval has been obtained from the Ethical Board Committee at the Third Affiliated Hospital of Sun Yat-sen University (II2023-119-01). The trial was pre-registered in Chinese Clinical Trials (ChiCTR2300072136) on 5 June 2023. The results of this trial will be actively disseminated through peer-reviewed publications and conference presentations. Any identifiable personal information will be anonymised to protect confidentiality.Protocol version 2.0, 31 July 2024.Trial registration number ChiCTR2300072136.